Growth traits of the Dorper sheep. II. Genetic and phenotypic parameters - Inyangala, B.A.O.; Rege, J.E.O.; Itulya, S. (International Livestock Centre for Africa, 1992)
Presents results of a study undertaken at Magogo, Kenya, to analyse genetic and phenotypic correlations between adjacent weights, between weights and rates of growth, and among growth rates themselves, hence data on 969 lambs collected over a 10-year period (1978-1987) on Dorper sheep were used in the study. Lamb traits studied were weights from birth to yearling and absolute growth rates between adjacent stages of growth.